Understanding academic performance abroad: Family background and cultural capital among Chinese students in Japanese higher education - Jiao, Ran (Journal of International Students, 2026)
This study investigates the influence of family background on the academic performance of Chinese international students by following twenty-one students over two years and employing a case study approach that integrates interviews and observations. This research develops an analytical framework for understanding academic success abroad, drawing on the concepts of cultural capital and academic engagement. Using constructive grounded theory and thematic analysis, the study examines students’ performance in three key areas: their ability to achieve high grades, their strategies for solving academic problems, and their classroom participation. The findings reveal that students from affluent families are more likely to draw on economic capital to address academic challenges and tend to express greater confidence in their views in class. However, students from working-class backgrounds rely more on independent reading to address academic questions and are more likely to remain passive in class rather than actively participating in discussions.